A novel approach for solar greenhouse air temperature and heating load prediction based on Laplace transform. (December 2021) - Huang, Lin; Deng, Lianhua; Li, Angui; Gao, Ran; Zhang, Linhua; Lei, Wenjun
Abstract: Solar greenhouses have provided favorable microclimates for improving and increasing crop production. As a significant factor of microclimates, greenhouse indoor air temperature has received extensive research attention in recent years. Although dynamic models were studied in diverse greenhouses, previous researches failed to consider the existing models' applicability, simplicity, and accurate boundary conditions for solar greenhouses. Hence, a dynamic thermal model based on Laplace transform was proposed for predicting solar greenhouse air temperature and heating load. The heat flux boundary conditions on interior surfaces of the greenhouse north wall and soil were revised by amending the solar fraction expressions with solar azimuth angle considered. The results indicated that the predicted air temperature was in good agreement with experimental values, and three evaluation indices of MAE, RMSE, and NRMSE were -1.250, 1.608, and 15.441%, respectively. Moreover, under three different indoor air conditions, the north wall and soil's heat transfer flux were analyzed, indicating that the north wall is the main loss part of the experimental greenhouse's opaque envelope. Besides, the results also demonstrated that the daily total heating load in Case 1 was larger than that in Case 3, which means different greenhouse air design temperature between day and night is more energy-saving in winter. Furthermore, the physical meaning of the air temperature solution expression and the limitations of this approach were also elaborated. The contribution of this study is to offer accurate temperature forecasting for solar greenhouses' heating, ventilation, and air conditioning applications in the future. Highlights: Solar fraction expressions were revised with the solar azimuth angle considered. Indoor air temperature and heating load were predicted based on Laplace transform. Different interior design temperatures day and night were recommended for solar greenhouse heating. The physical meaning of the greenhouse air temperature solution expression was analyzed.